The Role of Islamic Economics in Overcoming Economic Inequality Through Sharia Financial Technology in Stimulating Economic Growth - Salma Abubakar Supu; Indah Rizani (Global Scientific Publishing, 2023)
Inequality the global economy being one issue major problems faced by society international . In many countries, inequality This create sharp gap between rich and poor groups , hinder development sustainable, as well cause instability social and political. In context This, Islamic economics has significant role in overcome inequality global economy . Islamic economics does not only emphasize aspect justice social , but also provides framework holistic work For promote sustainability, inclusion , and distribution fair wealth . Study of economic growth can found in draft Islamic economics . Draft this is basically it has summarized Good in a way explicit nor implicit in the Koran , Sunnah and the thoughts of previous Islamic scholars , however emergence return draft this , in particular a number of decade later This especially related conditions of underdeveloped Muslim countries that require a special formula in strategy and planning its construction . Specificity growth and development in Islamic economics emphasizes very serious attention to development resource man at a time empowerment natural For increase honor and dignity man. This is not only realized in success fulfillment just material needs , but also needs and preparation welcome life afterlife .
Keywords: Role; fulfillment; strategy; construction